Complete trisomy 9 with unusual phenotypic associations: Dandy-Walker malformation, cleft lip and cleft palate, cardiovascular abnormalities - Gabriele Tonni; Mario Lituania; David Chitayat; Maria Paola Bonasoni; Sarah Keating; Megan Thompson; Patrick Shannon (Elsevier, 2014)
Objective: Trisomy 9 is a rare chromosomal abnormality usually associated with first-trimester miscarriage; few fetuses survive until the second trimester. We report two new cases of complete trisomy 9 that both present unusual phenotypic associations, and we analyze the genetic pathway involved in this chromosomal abnormality. Case report: The first fetus investigated showed Dandy-Walker malformation, cleft lip, and cleft palate) at the second trimester scan. Cardiovascular abnormalities were characterized by a right-sided, U-shaped aortic arch associated with a ventricular septal defect (VSD). Symmetrical intrauterine growth restriction and multicystic dysplastic kidney disease were associated findings. The second fetus showed a dysmorphic face, bilateral cleft lip, hypoplastic corpus callosum, and a Dandy-Walker malformation. Postmortem examination revealed cardiovascular abnormalities such as persistent left superior vena cava draining into the coronary sinus, membranous ventricular septal defect, overriding aorta, pulmonary valve with two cusps and three sinuses, and the origin of the left subclavian artery distal to the junction of ductus arteriosus and aortic arch. Conclusion: Complete trisomy 9 may result in a wide spectrum of congenital abnormalities, and the presented case series contributes further details on the phenotype of this rare aneuploidy.